2021
DOI: 10.1136/bcr-2020-236296
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram-induced epileptic seizures

Abstract: Disulfiram has been widely used for over six decades in the treatment of alcohol dependence, as an aversive therapeutic agent. Despite having very few side effects when taken without concurrent alcohol consumption, some of these may underlie serious clinical complications. Epileptic seizure induction is a rare adverse effect of disulfiram and its aetiological mechanism is unknown. We present a hospitalised 47-year-old male patient with two episodes of generalised tonic-clonic seizures during treatment with dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The disulfiram–ethanol reaction (DER) most often occurs during the first 12 h after administration and typically consists of facial flushing, perspiration, tachycardia, nausea, and vomiting. Severe reactions can lead to hypotension, respiratory depression, cardiovascular collapse, arrhythmias, seizure, or death [ 3 , 10 , 165 , 166 ]. A case report of two patients who developed shock from the disulfiram–ethanol reaction found that both developed watershed infarcts in the brain and one developed probable non-occlusive mesenteric ischemia [ 167 ].…”
Section: Resultsmentioning
confidence: 99%
“…The disulfiram–ethanol reaction (DER) most often occurs during the first 12 h after administration and typically consists of facial flushing, perspiration, tachycardia, nausea, and vomiting. Severe reactions can lead to hypotension, respiratory depression, cardiovascular collapse, arrhythmias, seizure, or death [ 3 , 10 , 165 , 166 ]. A case report of two patients who developed shock from the disulfiram–ethanol reaction found that both developed watershed infarcts in the brain and one developed probable non-occlusive mesenteric ischemia [ 167 ].…”
Section: Resultsmentioning
confidence: 99%